Hassadi and Problematic reference (Nature of philosophical practice) (Journal of Human Sciences, 2020)
This research aims to approach the philosophical practice of one of the most important thinkers in contemporary Libyan culture, he is Najeeb Al-Hasadi. He was distinguished by the abundance of his thinking product and the multiplicity of paths in which he is active. He also contributed to the formation of the awareness of a wide range of those involved in the field of philosophical studies In Libya> For this, it was necessary to stop at the product of thinking in order to try to diagnose the theoretical grounds on which it is based. We will try to do by diagnosing the problem that brings together the elements of the multiple paths in which his thinking is active. We also discuss the problematic diagnosis of the thinking discourse of the Hassadi. The state of stability and stillness refers to the state of turmoil and anxiety, which is the feature that usually characterizes thinking discourse characterized by novelty and originality.